Effects of crack position on fatigue life of large seamless storage vessels made of 4130X for hydrogen refueling station. (23rd August 2019) - Ma, Kai; Hua, Zhengli; Gu, Chaohua; Zhang, Zekun; Ye, Sheng; Yao, Yancheng
Abstract: Fatigue property of CrMo steel is significantly degraded by hydrogen embrittlement (HE), which probably influences the fatigue life of hydrogen storage vessels made of CrMo steel. In this study, tests of fatigue crack growth rate (FCGR) for specimens extracted from the cylinder, juncture and shoulder of a seamless storage vessel made of 4130X for hydrogen refueling station were performed in 45 MPa hydrogen gas. Based on the test results, a finite element method (FEM) based on adaptive grid technique was applied to calculate fatigue life of the vessel with an initial crack at different positions. 3D laser scanning technology was used to build the model which can well conform to the actual vessel. Results indicate that the FCGR of 4130X in 45 MPa hydrogen is approximately 10–15 times of the FCGR in air. The FCGR of specimens from the shoulder is approximately 1.2–1.5 times of that from the cylinder and juncture. However, as the influence of stress distribution, the fatigue life of a vessel with a crack in the middle of the cylinder is lower than that of the vessel which exists crack with the same size at the juncture and shoulder. Highlights: Fatigue crack growth rate of 4130X in 45 MPa hydrogen gas was obtained. A fatigue life calculation model for hydrogen storage vessel was established. The fatigue lives of vessel with a crack at different positions were calculated.